Different gender division patterns for swine housing in wean-to-finish system - Massari, Juliana M.; Vercellino, Rimena do A.; Curi, Thayla M.R.de C.; de Moura, Daniella J.; Medeiros, Brenda B.L.; Salgado, Douglas D'alessandro [UNESP] (My University, 2017)
This study aimed at identifying the best gender division pattern for swine at nursery stage, through the evaluation of behavioral and environmental parameters. Three treatments were established to achieve our objective: single-sex housing of 26 surgically castrated male pigs; mixed-sex housing of 13 castrated males and 13 females; and single-sex housing of 26 females. Environmental and behavioral data have been recorded. It was used an ethogram to make an inventory of behaviors and that was used in multivariate analysis. Bite addiction differed statistically among treatments, and the lowest occurrence was in mixed-sex housing. Results of the multivariate analysis suggested that regardless of the treatment chosen, relative humidity is positively associated with the production of gases and dry-bulb temperature with airspeed. Mixed-sex housing had multivariate relations suggesting less aggressive behaviors over food resources, being an example of social interaction that improves swine welfare.
Keywords: Behavior; Facilities; Multivariate analysis; Welfare